Picture Word Inductive Model (PWIM) for Increasing Students’ Vocabulary Mastery at SMP An-Nashr Malang - Mulis; Anisah Adiana (English Language Teaching Journal, 2025)
The data of this research were taken from tests (pre-test, and post-test). This test was done to know the differences of students’ achievement before and after teaching and learning using Picture Word Inductive Model (PWIM). Further, this research employed two cycles in which each cycle consisted of three meeting. In each cycle the students were given test (cycle 1 and cycle 2). To analyse the data, the proportion of correct answers was divided by the total scores. The aspects assessed include understanding meaning, use in sentences, vocabulary variety, vocabulary pronunciation, and use in context. The finding of this research revealed that the average score of students’ vocabulary mastery in pre-test was 49. This showed that students had lack of vocabulary mastery. Then, in post -test of cycle 1, the students’ average score got improvement. Keywords: Picture Word Inductive Model, Vocabulary Matery